2013
DOI: 10.1186/1475-2859-12-122
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced membrane protein expression by engineering increased intracellular membrane production

Abstract: BackgroundMembrane protein research is frequently hampered by the low natural abundance of these proteins in cells and typically relies on recombinant gene expression. Different expression systems, like mammalian cells, insect cells, bacteria and yeast are being used, but very few research efforts have been directed towards specific host cell customization for enhanced expression of membrane proteins. Here we show that by increasing the intracellular membrane production by interfering with a key enzymatic step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 30 publications
(35 reference statements)
4
53
0
Order By: Relevance
“…pah1 Δ) causes a 90% decrease in TAG levels of stationary phase S . cerevisiae cells (Han et al ., ), while similar results have been obtained with the putative Yl PAH1 deletion mutant (Guerfal et al ., ). Also, the S .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…pah1 Δ) causes a 90% decrease in TAG levels of stationary phase S . cerevisiae cells (Han et al ., ), while similar results have been obtained with the putative Yl PAH1 deletion mutant (Guerfal et al ., ). Also, the S .…”
Section: Resultsmentioning
confidence: 97%
“…pah1Δ ; Han et al ., ) and in a Y . lipolytica mutant where the putative Yl PAH1 was deleted (Guerfal et al ., ). Also, the lack of Sc PAH1 has severe consequences on cell physiology, as indicated by the fact that pah1Δ cells present serious growth defects (Han et al ., ; Park et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Previous work in Y. lipolytica showed that the lack of PAH1 decreases the TAG levels 5‐fold but increases the phospholipid levels 2‐fold in cells grown in oleic acid media (Guerfal et al, ). Also, the Y. lipolytica pah1 Δ mutant presented the typical phenotype of the ER expansion due to overproduction of phospholipids and a great decrease in the number of lipid droplets (Guerfal et al, ). These findings are in line with the phenotypes reported for the well‐studied S. cerevisiae pah1 Δ mutant grown in glucose (Fakas et al, ; Han et al, ; Han, Siniossoglou, & Carman, ).…”
Section: Discussionmentioning
confidence: 97%
“…As stated in a recent review,[5] identifying or engineering yeast strains with improved yield characteristics may either be targeted towards one particular pathway or may take a more global approach [98]. Examples of the targeted approach include ‘humanizing’ the yeast glycosylation[99] and sterol[100] pathways and modifying membrane phospholipid synthesis to proliferate intracellular membranes [101]. Studies taking a more global approach in both S. cerevisiae [102,103] and P. pastoris [91,104] have identified the importance of the unfolded protein response (the cellular stress response activated by the accumulation of unfolded or misfolded protein) and reduced translational activity in high‐yielding cultures.…”
Section: Designing Improved Recombinant Antigen Synthesis Experimentsmentioning
confidence: 99%